Dynamics of Morphological Change in Neonatal Ovarian Tissue During Hypothermic Storage Depending on Composition of Incubation Medium - Kiroshka, V. V.; Medinets, E. A.; Tischenko, Yu. O.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2024)
In this work we carried-out the comparative analysis of dynamics of morphological structure transformation of neonatal ovarian tissue during hypothermic storage (HS) in the media with different composition. It has been found that high pool of morphologically normal follicles (88%) was preserved in nonelectrolyte solutions, formation of degenerative follicles was of reversible character. In electrolyte solutions the quantity of morphologically normal follicles was lower (66%), the damages were accompanied by the formation of irreversible degenerative forms of follicles. It has been demonstrated experimentally that the neonatal ovarian tissue after the one day of HS in nonelectrolyte solutions had the ability to restore its function post heterotopic transplantation.